Alternation between toxic and proliferative effects of Roundup® on human thyroid cells at different concentrations - Dal’ Bó, Izabela Fernanda; Teixeira, Elisângela Souza; Rabi, Larissa Teodoro; Peres, Karina Colombera; Nascimento, Matheus; Chiamolera, Maria Izabel; Máximo, Valdemar; Bufalo, Natássia Elena; Ward, Laura Sterian (Frontiers in Endocrinology, 2022)
Endocrine-disrupting and carcinogenic effects of glyphosate have long been suspected, but little is known about the effect of compounds used in real life at different concentrations, neither in normal nor in thyroid tumor cells. As cancer cells may have different sensitivities and the effect of the product containing glyphosate may be different from that produced by the active ingredient alone, including the Acceptable Occupational Exposure Level (AOEL=160µg/L) and the Acceptable Daily Intake (ADI=830µg/L) determined by ANVISA, we used two human thyroid-derived cell lines, Nthy-ori 3-1 (from normal follicular cells) and TPC-1 (from papillary carcinoma), to test 15 different concentrations of Roundup® Original DI. Trypan blue (TB), CCK-8 and BrdU assays were used to evaluate cytotoxicity, metabolic activity and proliferation with 24h and 48h exposures in technical and biological triplicates. TB showed an important toxic effect, especially after 24h of exposure, in both cell lines. The AOEL concentration caused the death of 43% and 50% of the Nthy-ori and TPC-1 cells, respectively, in 24 h, while ADI resulted in 35% and 58% of cell death. After 48h of exposure, AOEL and ADI caused a lower number of dead Nthy-ori (33% and 18%) and TPC-1 (33% and 37%) cells, respectively, suggesting that the toxic effect of the product disappears and/or both strains have repair mechanisms that protect them from longer exposures. On the other hand, the CCK-8 assay showed that small concentrations of Roundup have a proliferative effect: 6.5µg/L increased the number of both Nthy-ori and TPC-1 cells at 24h, and the BRDU assay confirmed the stimulatory effect with a 321% increase in the absorbance of Nthy-ori cells at 48h. The herbicide produced even more frequent increases in the BRDU absorbance of TPC-1 cells, mainly at 24h. We conclude that thyroid cells exposed to Roundup present a nonmonotonic dual dose–response curve. Low concentrations of the pesticide, considered acceptable, cause significant cell death but also have an important proliferative effect, especially on TPC-1 cells. This herbicide, widely used around the world, may play a role in the increased incidence rate of thyroid nodules and cancer that has been observed in recent decades.